2019
DOI: 10.1681/asn.2018070756
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Coiled-Coil Assembly to Ca2+/Calmodulin-Dependent Inactivation of TRPC6 Channel and its Impacts on FSGS-Associated Phenotypes

Abstract: BackgroundTRPC6 is a nonselective cation channel, and mutations of this gene are associated with FSGS. These mutations are associated with TRPC6 current amplitude amplification and/or delay of the channel inactivation (gain-of-function phenotype). However, the mechanism of the gain-of-function in TRPC6 activity has not yet been clearly solved.MethodsWe performed electrophysiologic, biochemical, and biophysical experiments to elucidate the molecular mechanism underlying calmodulin (CaM)-mediated Ca2+-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Likewise, receptor agonist-evoked TRPC3 current was strongly inhibited by the rise in [Ca 2+ ] c (Thyagarajan et al, 2001). The mechanisms for the Ca 2+ -dependent inhibition may involve both CaM-dependent and CaMindependent processes (Polat et al, 2019;Shi et al, 2004) with the IC 50 of Ca 2+ inhibition of TRPC7 being ~10 time lower than that of TRPC6. Single channel studies revealed that millimolar extracellular Ca 2+ also suppressed the unitary conductance of TRPC6 and C7 at negative potentials, again with sensitivity higher for TRPC7 than C6 (Shi et al, 2004).…”
Section: Ca 2+ mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, receptor agonist-evoked TRPC3 current was strongly inhibited by the rise in [Ca 2+ ] c (Thyagarajan et al, 2001). The mechanisms for the Ca 2+ -dependent inhibition may involve both CaM-dependent and CaMindependent processes (Polat et al, 2019;Shi et al, 2004) with the IC 50 of Ca 2+ inhibition of TRPC7 being ~10 time lower than that of TRPC6. Single channel studies revealed that millimolar extracellular Ca 2+ also suppressed the unitary conductance of TRPC6 and C7 at negative potentials, again with sensitivity higher for TRPC7 than C6 (Shi et al, 2004).…”
Section: Ca 2+ mentioning
confidence: 99%
“…Single channel studies revealed that millimolar extracellular Ca 2+ also suppressed the unitary conductance of TRPC6 and C7 at negative potentials, again with sensitivity higher for TRPC7 than C6 (Shi et al, 2004). A recent study indicates that CaM mediates Ca 2+ -dependent inactivation of TRPC6 by altering the assembly of the C-terminal coiled-coil domain, where gain-of-function TRPC6 mutations have been found from patients with focal segmental glomerulosclerosis (FSGS) (Polat et al, 2019). For TRPC4 and C5, Ca 2+ was shown to either inhibit channel activation or accelerate current inactivation at concentrations higher than that needed to support the channel opening (Gross et al, 2009;Ordaz et al, 2005;Thakur et al, 2016).…”
Section: Ca 2+ mentioning
confidence: 99%
“…Given the indirect nature of GWAS, the known association of rare missense variants in TRPC6 with the genetic form of chronic kidney disease, focal segmental glomerular sclerosis (FSGS) ( 24 , 25 ), and the fact that FSGS can result from exposure to anthracyclines ( 26 ), we sequenced the coding regions of TRPC6 in 38 patients with CRHF. None of the confirmed causative FSGS mutations were identified in patients with CRHF.…”
Section: Resultsmentioning
confidence: 99%
“…It is caused by the impairment of the Ca 2+ -dependent inactivation, resulting from the disruptions of TRPC6's coiled-coil assembly. The excessive Ca 2+ may contribute to structural damage in the podocytes [31]. Systematic analysis of TRPC6-related mutations showed that loss-of-function (LOF) of TRPC6 has the potential to induce disease [32], which may cause FSGS earlier than in GOF-type TRPC6 patients by interacting with actin cytoskeleton rearrangement during podocyte development [33].…”
Section: The Role Of Trpcs In Kidney Diseasementioning
confidence: 99%